2012
DOI: 10.1051/fruits/2012035
|View full text |Cite
|
Sign up to set email alerts
|

Major physicochemical and antioxidant changes during peach-palm (Bactris gasipaesH.B.K.) flour processing

Abstract: Major physicochemical and antioxidant changes during peach-palm (Bactris gasipaes H.B.K.) flour processing. Abstract-Introduction. Several studies have demonstrated that food processing affects nutrients such as bioactive compounds, protein, starch, fat, fiber, minerals and antioxidant capacity. Our study examined how heat changes the physicochemical composition and antioxidant capacity of peach-palm fruit (Bactris gasipaes H.B.K.) during flour production. Materials and methods. Five commercial batches of frui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
(60 reference statements)
4
16
1
3
Order By: Relevance
“…The pH and the acidity of the flour presented values close to those reported by Rojas-Garbanzo et al (2012) for peach palm, raw, cooked and in flour ( Table 1). The dry mass value for peach palm mesocarp flour reported by Dliveira et al (Table 1) and the existence of pigments generated during the dehydration process in the sample.…”
Section: Physicochemical Analysis Of Peach Palm Peel Floursupporting
confidence: 64%
“…The pH and the acidity of the flour presented values close to those reported by Rojas-Garbanzo et al (2012) for peach palm, raw, cooked and in flour ( Table 1). The dry mass value for peach palm mesocarp flour reported by Dliveira et al (Table 1) and the existence of pigments generated during the dehydration process in the sample.…”
Section: Physicochemical Analysis Of Peach Palm Peel Floursupporting
confidence: 64%
“…However, a comparison of the daily intake with the input from peach palm fruits can be made after the fruit has been cooked (the traditional preparation method in Costa Rica), because a thermal process is necessary due to the presence of anti-nutritional factors such as lectins, some polyphenols, saponins, oxalic acid, and some amylase and trypsin inhibitors (ROJAS-GARBANZO et al, 2011). It has been reported that the protein content of peach palm fruits is not affected by cooking (30 min in boiling water), the final protein content of cooked peach palm pulp being 5.0 ± 1.1 g/100 g dw (ROJAS-GARBANZO et al, 2012).…”
Section: Physicochemical and Antioxidant Composition Of Fresh Peach Pmentioning
confidence: 99%
“…Peach palm fruit has received different names such as pejibaye in Costa Rica, chontaduro in Venezuela and Colombia, pibá in Panamá, pupunha in Brazil, and peach palm in English‐speaking countries . Historically, the largest producers of peach palm fruit are Colombia, Brazil, Peru, and Costa Rica, being cultivated as small holders in agroforestry systems or as monocultures .…”
Section: Introductionmentioning
confidence: 99%